Espaço em movimento : a (trans)formação do espaço mineiro a partir da análise do sistema Sesmarial (Minas Gerais, 1701-1836) - Rodrigo Paulinelli de Almeida Costa (2020)
The Portuguese economy, since the end of the Iberian Union, entered a crisis. To try to solve the economic problems, numerous expeditions were promoted to the interior of Brazil in search of natural and mineral wealth. Within this exploratory logic, the occupation of Minas Gerais was established as of the end of the 17th century. From that moment on, people from all regions of the empire gradually occupied the Generals in search of gold, other economic activities and rapid enrichment. To control this exploration and territorial expansion, the Crown adopts the Portuguese Crown land concessions, which consisted of the donation of a land improvement to those willing to colonize the territory and make it productive in some way. From this perspective, this thesis aims to investigate the formation of the Minas Gerais space from this kind of land concession. For this, a thorough analysis of the Inventário das Cartas de Sesmarias was made available in the Arquivo Público Mineiro, this inventory, which contains the description of all the Portguese Crwon land concession that were distributed in Minas Gerais. With the creation of a database made from the transcription of this inventory, it was possible to establish dialogues with the History of Minas, comprising each economic moment throughout the 18th and early 19th centuries, relating them to the spatial occupation of the Captaincy. Through the techniques of georeferencing and Space History, it was possible to establish important aspects of the relationship between History and Geography, as well as the understanding of formation and spatial transformation. Finally, the Sesmariasl system was analyzed, evaluating its distribution over periods, by type of donations, the titles of sesmeiros, in order to understand how this system relates to the economic and social formation of Minas Gerais and trying to understand what shape the space is formed from the socioeconomic needs of each region. From these analyzes, it was concluded that the space of Minas Gerais followed the movements of economic activities in each region over time, realizing the expansion of the frontiers of mining occupation and the retraction of the frontiers of the hinterland, from the understanding that these they are not static and are constantly changing.